2016
DOI: 10.1063/1.4940974
|View full text |Cite
|
Sign up to set email alerts
|

Venting temperature determines surface chemistry of magnetron sputtered TiN films

Abstract: Surface properties of refractory ceramic transition metal nitride thin films grown by magnetron sputtering are essential for resistance towards oxidation necessary in all modern applications. Here, typically neglected factors, including exposure to residual process gases following the growth and the venting temperature T-v, each affecting the surface chemistry, are addressed. It is demonstrated for the TiN model materials system that T-v has a substantial effect on the composition and thickness-evolution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 32 publications
(32 reference statements)
1
43
0
Order By: Relevance
“…The deposition time on amorphous carbon substrates was 5 min and on sapphire 30 min, where the first samples were used to enable optimum Rutherford back-scattering spectrometry (RBS) measurements conditions while the second set was used for nanoindentation, thermal stability and atom probe investigations. In order to avoid surface oxidation [43], all samples were cooled in vacuum and taken out of the deposition system only when the temperature was below 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…The deposition time on amorphous carbon substrates was 5 min and on sapphire 30 min, where the first samples were used to enable optimum Rutherford back-scattering spectrometry (RBS) measurements conditions while the second set was used for nanoindentation, thermal stability and atom probe investigations. In order to avoid surface oxidation [43], all samples were cooled in vacuum and taken out of the deposition system only when the temperature was below 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…The vacuum chamber is vented at the substrate temperature lower than 180 °C to allow for a better control of surface chemistry upon air exposure. 27 Four different powering schemes are employed to deposit four series of V1-xAlxN films with varying Al/(Al+V) ratio x, with distinctly different ion irradiation conditions during growth. Two first series are obtained using a hybrid process in which one of the targets is operated in HIPIMS mode, while the other runs as a conventional magnetron (Al-HIPIMS/V-DC and V-HIPIMS/Al-DC).…”
Section: Film Growthmentioning
confidence: 99%
“…It can be concluded that the venting temperature is an important and influential parameter for the surface chemistry of carbide nanocomposites. An analogous effect has also been demonstrated for TiN [40]. Conversely, it may possible to reduce these oxides by vacuum annealing, as has been done for air-exposed Ni 3 C/a-C coatings [41].…”
Section: Surface Characterization Of Coatingsmentioning
confidence: 78%